POSITIVE PSYCHOLOGY AND THE STUDY OF FEAR OF HAPPINESS: CHARACTER STRENGTHS, MENTAL ANXIETY, AND DEFENCE MECHANISM REACTIVITY (International Journal of Food and Nutritional Sciences, 2022)
Recent developments in academic psychology have given rise to a new field known as "positive psychology," which expands the purview of scientific psychology to include the factors that contribute to people's happiness and success. The study of positive traits and qualities is central to positive psychology. Pursuing pleasure as a topic for thought and philosophy predates modern times. What constitutes pleasure and how one might get it are concepts that have undergone a significant transformation. A successful and fulfilling life is often used as a proxy for happiness. Well-being theories of the present day provide an alternative to conventional psychology by focusing on positive attributes rather than deficits. The opposites of sadness and happiness were shown to be the best predictors of the fear of happiness. Confidence-filled people reported greater levels of enjoyment and less despair than their apprehensive counterparts.